2002
DOI: 10.1080/00914030213025
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Properties Relationships for Bisphenol A Polycyanurate Network Modified with Polyoxytetramethylene Glycol

Abstract: A series of polycyanurate networks (PCNs), based on the dicyanate of bisphenol A monomer (DCBA), were synthesized in the presence of dierent contents of hydroxylterminated polyoxytetramethylene glycol (PTMG). The chemical structure, T g behaviour, modulus-composition relations and mechanical properties of the modi®ed PCNs were investigated by Fourier transform infrared (FTIR) spectroscopy, dynamic mechanical thermal analysis (DMTA) and mechanical testing. The oligomer modi®er in¯uences the structure of the ®na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…First, during the mixing procedure, the -OCN groups of DCBE could react with hydroxyl groups of [HEAIm][Cl] with formation of imidocarbonate O-C(=NH)-O fragment ( Figure 6, compound 2), which further reacted with a second DCBE molecule with formation of a stabilized dimer ( Figure 6, compound 3) Figure 6, compound 6) with release of ROH (monocyanate of bisphenol E). According to Grigat and Pütter [36] as well as our previous works [33][34][35], the more acidic phenol compared to alcohol was released, and thus, a substituted triazine ring should be obtained with the release of a monophenol derived from DCBE. Moreover, we presumed that [HEAIm][Cl] could also increase the polarization of the C=N bond in the imidocarbonate (Figure 6, compound 2), thus making the carbon atom of this functional group more electrophilic.…”
Section: Cer/il Curing Mechanismsmentioning
confidence: 97%
See 2 more Smart Citations
“…First, during the mixing procedure, the -OCN groups of DCBE could react with hydroxyl groups of [HEAIm][Cl] with formation of imidocarbonate O-C(=NH)-O fragment ( Figure 6, compound 2), which further reacted with a second DCBE molecule with formation of a stabilized dimer ( Figure 6, compound 3) Figure 6, compound 6) with release of ROH (monocyanate of bisphenol E). According to Grigat and Pütter [36] as well as our previous works [33][34][35], the more acidic phenol compared to alcohol was released, and thus, a substituted triazine ring should be obtained with the release of a monophenol derived from DCBE. Moreover, we presumed that [HEAIm][Cl] could also increase the polarization of the C=N bond in the imidocarbonate (Figure 6, compound 2), thus making the carbon atom of this functional group more electrophilic.…”
Section: Cer/il Curing Mechanismsmentioning
confidence: 97%
“…The spectrum of CER/[OMIm][BF 4 ] showed only characteristic absorbance bands of both individual components (see Figure 4, curve (3) was proposed for the formation of cyanurate cycles from DCBE polymerization being catalyzed by [HEAIm][Cl] ( Figure 6). Our hypothesis was based on the well-known mechanisms of polycyclotrimerization of CERs in the presence of hydroxy [1,[32][33][34][35] and amino [36,37] compounds. First, during the mixing procedure, the -OCN groups of DCBE could react with hydroxyl groups of [HEAIm][Cl] with formation of imidocarbonate O-C(=NH)-O fragment ( Figure 6, compound 2), which further reacted with a second DCBE molecule with formation of a stabilized dimer ( Figure 6, compound 3) Figure 6, compound 6) with release of ROH (monocyanate of bisphenol E).…”
Section: Cer/il Curing Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] Recently, we have published several papers dealing with the modification of PCNs by dihydroxy-telechelic polyethers or polyesters. [8][9][10][11] It was found that the modifiers were partly chemically incorporated into the PCN structure through the reaction of their terminal hydroxyl groups with cyanate groups of growing PCN network.…”
Section: Introductionmentioning
confidence: 99%
“…(3) Application of reactive elastomers, for instance, thermoplastic resin and rubber with active functional groups . (4) Block copolymerization with polyhydric alcohol, including polyether or polyester polyol . The main aim of the above modifications is to control the molecular structure or morphological structure, which is necessary to achieve significant toughening.…”
Section: Introductionmentioning
confidence: 99%